Pengaruh Pola Asuh Orang Tua Terhadap Pelaksanaan Sholat Remaja Pada Masa Pandemi Covid 19 Di Kenagarian Ampek Koto Palembayan Kabupaten Agam - Vina Hermawati; Iswantir; Pendi Hasibuan; Muhiddinur Kamal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
This research is motivated by the fact that there are still many children who are negligent in praying and even they do not pray, seen at the time of prayer, there are still many who play, watch television, sit in stalls and play games which are rampant in this day and age. only a small number of them pray in the mosque when the call to prayer is sounded and pray in their respective homes, and it can also be seen from the work of the parents of these children that there are employees, traders, and farmers, the majority of parents from the children work as farmers who go in the morning and return in the afternoon. The purpose of this study was to find out how the parenting style of parents and also how the implementation of youth prayers in Kenagarian Ampek Koto Palembayan, Agam Regency, and also to find out how much influence parenting has on the implementation youth prayer during the covid19 pandemic. The research used a correlational type of quantitative approach. Correlation is a type of research that aims to see and describe the influence between two research variables. The population in this study were all junior high school students aged 12-15 years in Ampek Koto Palembayan district, Agam Regency. The sampling used in this study is random sampling, the determination of the sample size is taken from 25% of the population. The data were collected using a questionnaire with a Likert scale, the data analysis technique used the formula r product moment, the correlation coefficient and the coefficient of determination while the analysis test conditions used normality, linearity and homogeneity tests. From the results of research on parenting patterns during the covid 19 pandemic in Kenagarian Ampek Koto Palembayan, Agam Regency, the results showed that parenting was in the moderate category at 79.5%. in Kenagarian Ampek Koto Palembayan, Agam Regency, the results of the implementation of youth prayers are classified into the medium category of 87.2%. The results of the correlation test can be seen that rcount 0.478 > rtable 0.316 with a degree of freedom (Df) 39 at a significant level of 0.05. Based on the results of the study, Ho is rejected and Ha is accepted, so it can be seen that there is a significant influence between parenting parent on the implementation of adolescent prayer with a